2018
DOI: 10.1177/2050313x18772125
|View full text |Cite
|
Sign up to set email alerts
|

Delayed photosensitivity in a child with erythropoietic protoporphyria : a case report

Abstract: Erythropoietic protoporphyria (EPP) is a genetically inherited disease that causes protoporphyrin accumulation in erythrocytes, skin, liver, bile, and stool. Clinically this manifests as photosensitivity with painful, edematous cutaneous porphyria. We present the case of a four-year-old boy with a delayed photosensitivity reaction to sunlight. In the evening following sun exposure, he would develop swelling and a violaceous rash on the dorsal surface of his hands and occasionally the helix of his ears. His rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…This triggers reactive oxygen species production and complement activation, both of which lead to inflammatory changes [48,49]. It has been reported that a daily oral regimen of cimetidine markedly improved cutaneous photosensitivity in four pediatric patients with EPP [37,38]. However, the EPP-causing FECH mutations were documented in only one of these patients [37], and PPIX was measured before and after cimetidine administration in another single patient [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This triggers reactive oxygen species production and complement activation, both of which lead to inflammatory changes [48,49]. It has been reported that a daily oral regimen of cimetidine markedly improved cutaneous photosensitivity in four pediatric patients with EPP [37,38]. However, the EPP-causing FECH mutations were documented in only one of these patients [37], and PPIX was measured before and after cimetidine administration in another single patient [38].…”
Section: Discussionmentioning
confidence: 99%
“…Given recent reports that cimetidine improved cutaneous photosensitivity in patients with EPP, presumably by inhibiting ALAS activity in erythroid cells [36][37][38], we investigated whether cimetidine inhibits ALAS2 activity, first in vitro and then in bone marrow cells isolated from cimetidine-treated mice. Human ALAS2 enzyme (NP_001033057.3) was prokaryotically expressed and purified, and its activity was measured in the presence of increasing concentrations (0 to 240 µmol/L) of cimetidine (Table 1).…”
Section: Cimetidine Does Not Alter Activity or Expression Of Alas Or ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Erythropoietic protoporphyria (EPP) is a genetic porphyria caused by a deficiency of the enzyme ferrochelatase. The population prevalence ranges from 1 in 75 000‐200 000, and it is the most common porphyria in children . It is one of the two subtypes of protoporphyria, the other being delta‐aminolevulinic acid synthase 2 hyperactivity, also known as X‐linked protoporphyria (XLP).…”
Section: Discussionmentioning
confidence: 99%